Costs and Earnings of Fishing Efforts of Marine Set-Bag-Net (MSBN) Fisheries of Bangladesh (Journal of Agriculture & Rural Development, 2008)
DOI = 10.3329/jard.v5i1.1476 J Agric Rural Dev 5(1&2), 176-178, June 2007